Dependence rate of smokers in undergraduate dental school - Afianita, Dea Eka; Susilawati, Sri; Sutardjo, Dede (Padjadjaran Journal of Dentistry, 2014)
Introduction: The habit of smoking, can cause dependence for smokers and also it can cause various diseases and health problems, both physical health and oral health. Smoking habits are also occured in the health students which they should show good example to the community to live a healthy lifestyle, including a role as well as to reduce their smoking habits, and also providing information to the effects of smoking. The purpose of this study was to determine the dependence rate of smoking in undergraduate Dental School Faculty of Dentistry, Padjadjaran University. Methods: This study was a descriptive type using the survey technique. Sampling was conducted with a snowball technique. The sample of 39 smokers comprising 24 men and 15 women. Respondents filled in questionnaires and the responses to questionnaires have different points to determine the level of smoking dependence. Results: The results shows that about 76.9% of the total sample included in the category of dependence rate of smoking are very low, 20.5% with a lower category, and 2.6% with the medium category. Conclusion: Smoker students in undergraduate Dental School has a very low level of dependence.